A PCR-free technology to detect and quantify microRNAs directly from human plasma. Issue 23 (9th November 2018) - Marín-Romero, Antonio; Robles-Remacho, Agustín; Tabraue-Chávez, Mavys; López-Longarela, Bárbara; Sánchez-Martín, Rosario M.; Guardia-Monteagudo, Juan J.; Fara, Mario A.; López-Delgado, Francisco J.; Pernagallo, Salvatore; Díaz-Mochón, Juan J.
Abstract : A novel and unique method for a PCR/label-free detection and absolute quantification of miR-451a in blood samples. Abstract : A novel sensitive, specific and rapid method for the detection and quantification of microRNAs without requiring extraction from their biological sources is now available using a novel chemical based, PCR-free technology for nucleic acid testing. In this study, we both demonstrate how this method can be used to profile miR-451a, an important miRNA in erythropoiesis, and compare with the gold standard RT-qPCR.